Factors associated with the incidence of pressure ulcer during hospital stay - Matozinhos, Fernanda Penido; Velasquez-Melendez, Gustavo; Tiensoli, Sabrina Daros; Moreira, Alexandra Dias; Gomes, Flávia Sampaio Latini (Revista da Escola de Enfermagem da USP, 2017)
OBJECTIVE Estimating the incidence rate of pressure ulcers and verifying factors associated with this occurrence in a cohort of hospitalized patients. METHOD This is a cohort study in which the considered outcome was the time until pressure ulcer occurrence. Estimated effect of the variables on the cumulative incidence ratio of the outcome was performed using the Cox proportional hazards model. Variable selection occurred via the Logrank hypothesis test. RESULTS The sample consisted of 442 adults, with 25 incidents of pressure ulcers. Patients with high scores on the Braden scale presented a higher risk of pressure ulcer incidence when compared to those classified into the low score category. CONCLUSION These results reinforce the importance of using the Braden Scale to assist in identifying patients more likely to develop pressure ulcers.